Synthesis and properties of poly(arylene ether)s based on 3-pentadecyl 4,4'-biphenol - Tawade, Bhausaheb V.; Shaligram, Sayali V.; Valsange, Nitin G.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Polymer International, 2016)
A new biphenol, 3-pentadecyl 4,4-biphenol, was synthesized starting from 3-pentadecylphenol and was polycondensed with 4,4-difluorobenzophenone, 1,3-bis(4-fluorobenzoyl)benzene and bis(4-fluorophenyl)sulfone to obtain poly(arylene ether)s with biphenylene linkages in the backbone and pendent pentadecyl chains. Inherent viscosities and number-average molecular weights (M-n) of the poly(arylene ether)s were in the range 0.50 - 0.81 dL g(-1) and 2.2 x 10(4) - 8.3 x 10(4), respectively. Detailed NMR spectroscopic studies of the poly(arylene ether)s indicated the presence of constitutional isomerism which existed because of the non-symmetrical structure of 3-pentadecyl 4,4-biphenol. The poly(arylene ether)s readily dissolved in common organic solvents such as dichloromethane, chloroform and tetrahydrofuran and could be cast into tough, transparent and flexible films from their chloroform solutions. The poly(arylene ether)s exhibited T-g values in the range 35-60 degrees C which are lower than that of reference poly(arylene ether)s without pentadecyl chains. The 10% decomposition temperatures (T-10) of the poly(arylene ether)s were in the range 410-455 degrees C indicating their good thermal stability. A gas permeation study of poly(ether sulfone) containing pendent pentadecyl chains revealed a moderate increase in permeability for helium, hydrogen and oxygen. However, there was a large increase in permeability for carbon dioxide which could be attributed to the internal plasticization effect of pendent pentadecyl chains. (c) 2016 Society of Chemical Industry
Keywords: cashew nut shell liquid (CNSL); gas permeation study; pentadecyl; poly(arylene ether)s; thermal stability

Synthesis, characterization, and gas permeation properties of adamantane-containing polymers of intrinsic microporosity - Shrimant, Bharat; Shaligram, Sayali V.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
A new bis(catechol) monomer, namely, 4,4-((1r,3r)-adamantane-2,2-diyl)bis(benzene-1,2diol) (THADM) was synthesized by condensation of 2-adamantanone with veratrole followed by demethylation of the formed (1r,3r)-2,2-bis(3,4 dimethoxyphenyl)adamantane. Polycondensation of THADM and various compositions of THADM and 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethylspirobisindane was performed with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain the homopolymer and copolymers. These polymers demonstrated good solubility in common organic solvents such as dichloromethane, chloroform, and tetrahydrofuran and could be cast into tough films from their chloroform solutions. GPC analysis revealed that number average molecular weights of polymers were in the range 48,100-61,700 gmol(-1), suggesting the formation of reasonably high molecular weight polymers. They possessed intrinsic microporosity with Brunauer-Emmett-Teller (BET) surface area in the range 703-741 m(2)g(-1). Thermogravimetric analysis of polymers indicated that 10% weight loss temperature was in the range 513-518 degrees C demonstrating their excellent thermal stability. THADM-based polymer of intrinsic microporosity (PIM) showed P(CO2)=1080, P(O-2)=232 and appreciable selectivity [(CO2/CH4)=22.6, (CO2/N-2)=26.7, and (O-2/N-2)= 5.7]. The gas permeability measurements revealed that with increase in the content of adamantane units in PIMs, selectivity increased and permeability decreased, following the trade-off relationship. The gas separation properties of PIMs containing adamantane units were located close to 2008 Robeson upper bound for gas pairs such as CO2/CH4, CO2/N-2, H-2/N-2, and O-2/N-2. (c) 2017 Wiley Periodicals, Inc.
Keywords: adamantane; Gas permeation; intrinsic microporosity; membranes; structure-property relations